Do deposit insurance systems promote banking stability? - Nafis Alam; Ganesh Sivarajah; Muhammad Ishaq Bhatti (International Journal of Financial Studies, 2021)
During the global financial crisis (GFC), regulators and policymakers turned to deposit insurers, along with monetary and fiscal measures, to help restore market confidence and promote financial stability. These events have focused attention on the role of deposit insurers and their role in the banking system. Recent literature reveals that during the GFC, deposit insurance maintained banking stability and successfully prevented customers doing 'runs' on the banks. The objective of this paper is to examine the deposit insurance system's coverage limits and the impact on banking stability, in the context of a jurisdiction's economic and institutional environment. Our model examines 61 jurisdictions in Asia and Europe with explicit deposit insurance systems, covering the pre- and post-GFC period between 2004 and 2014. We also examine subsets to investigate the effects of the region by comparing Asia and Europe, as well as a subset using the date of establishment of the deposit insurance system to understand if maturity matters. The results indicate that deposit insurance systems, and specifically deposit insurance coverage levels, have both positive and negative effects on banking stability. We find significant associations with certain economic and institutional factors; however, there are differences between the models we ran. These can be ascribed to regional factors and the date of when a deposit insurance system was established.
Keywords: 330; banking; deposit insurance; financial crisis; financial stability